Peran Religiusitas dalam Memoderasi Persepsi, Preferensi dan Pengetahuan Terhadap Minat Menjadi Nasabah di Bank Syariah Indonesia - Mayogi Araffi; Slamet Haryono (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to test the influence of perception, preference and knowledge on the interest of being a customer in Islamic banks with religiosity as a moderation variable. This research uses a type of field research with a quantitative approach. The data source in this study is primary data obtained from the results of questionnaires with assessments using the likert scale. The population in this study was 100 respondents. In data analysis, the data analysis technique used is regression analysis in moderation. The results showed that perception affects the interest in becoming a customer, but preferences and knowledge have no effect on the interest in becoming a customer. Then religiosity can moderate the perception of interest in being a customer, while religiosity cannot moderate preferences and knowledge of interests in becoming a customer.